Interconnection Disputes : Antitrust or Sector Regulation and the Case of New Zealand - Kerf, Michel; Neto, Isabel; Geradin, Damien (World Bank, Washington, DC, 2012)
Full liberalization of telecommunications markets provides scope for relying largely on general antitrust rules and institutions for economic regulation. But at least for a time after liberalization, sector-specific rules and institutions are likely to be needed in some areas, including interconnection. This Note draws lessons from the experience of New Zealand. After fully liberalizing its telecommunications market in the late 1980s, the country relied primarily on antitrust instruments to regulate interconnection until 2001, when it introduced a new regime putting heavier emphasis on sector-specific regulation.